Southeast Asian Islamic Art and Architecture: Re-Examining The Claim of the Unity and Universality of Islamic Art - Lien Iffah Naf’atu Fina (Universitas Islam Negeri Sunan Kalijaga, 2018)
This paper re-examines the claim of unity and universality of Islamic art, whose discussion usually disregards Islamic art and architecture in the Southeast Asian context. The question raised is where Islamic art in the Malay world should be put before the claim of the unity and universality of Islamic art and whether this claim is, thus, still valid. To meet this objective, the two heritages of Javanese Islamic art, Demak and Cirebon mosques and wayang, are presented and analyzed before such universal claim and pre-Islamic Javanese art. These Javanese expressions have unique features compared to those from the older Muslim world. The mosques lack geometric ornamentation and Qur’anic calligraphic decoration, and are rich with symbolism. However, both the mosques and wayang also clearly express the figurative designs. Thus, this paper argues that instead of geometric designs as the unified character of Islamic art as some argue, it should be the abstraction of motifs. This way, the universal claim of Islamic art accommodates the artistic expressions from the wider regions, including those from Southeast Asia. Besides the abstraction, these Javanese artistic expressions also shares other universal character of traditional development of Islamic art; its ability to always considering the local tradition while maintaining the basic principle of Islamic art. Javanese Islamic art is both Islamic and uniquely Javanese. In the midst of globalization and the contemporary tendency towards “Islamic authentication” by importing culture and tradition from the Middle East, including the mosque architecture, the latter character is vital. It tells that any direct import and implantation of other or foreign traditions to a certain region without any process of considering the local tradition and context has no basis and legitimation in Islamic artistic tradition.